Development of Mind Mapping Media to Teach English Speaking Skill: English - Ferdi Putra; Siti Rofi'ah; Istina Atul Makrifah (Journal of English Development, 2023)
The objective of the study is to determine processes. and outcomes of using mind mapping to teach English speaking skills for explaining text content in MA Ma'arif Ponggok eleventh grade. Students study a variety of topics at school, including languages. English is one of the languages that students learn at school. The utilization of media is one of the most effective strategies to aid student learning. The ADDIE paradigm is used in this form of study, known as study and Development (R&D). Data for this research were collected by observation, interviews, and a questionnaire.  The researcher obtains a score for validating instruments, media, and materials. The instrument validation score is 82.5%, which means "valid," the score for media expert validation is 90%, which means "very valid," and the score for material expert validation is 87.5%, which indicates "very valid." Aside from that, the students' replies to the media received a score of 79.65%, which signifies "very valid".